Asymptomatic Lymphocytic Interstitial Pneumonia with Extensive HRCT Changes Preceding Sjogren's Syndrome. (8th January 2021) - Baharuddin, Hazlyna; Hanafiah, Mohammad; Aflah, Syazatul Syakirin Sirol; Zim, Mohd Arif Mohd; Ch'Ng, Shereen Suyin
Abstract : Lymphocytic interstitial pneumonia (LIP) is a rare condition, commonly associated with Sjogren's syndrome (SS). We report a 53-year-old woman with an incidental finding of an abnormal chest radiograph. LIP was diagnosed based on high-resolution computed tomography and lung biopsy, but treatment was not initiated. Six years later, she developed cough and dyspnoea, associated with dry eyes, dry mouth, and arthralgia. While being investigated for the respiratory symptoms, she developed cutaneous vasculitis and was treated with 1 mg/kg prednisolone, which resulted in the improvement of her respiratory symptoms. Physical examination revealed fine bibasal crepitations, active vasculitic skin lesions, and a positive Schirmer's test. Investigations revealed a restrictive pattern in the pulmonary function test, stable LIP pattern in HRCT, and positive anti-Ro antibodies. She was treated with prednisolone and azathioprine for 18 months, and within this time, she was hospitalised for flare of LIP, as well as respiratory tract infection on three occasions. During the third flare, when she also developed cutaneous vasculitis, she agreed for prednisolone but refused other second-line agents. To date, she remained well with the maintenance of prednisolone 2.5 mg monotherapy for more than one year. The lessons from this case are (i) patients with LIP can be asymptomatic, (ii) LIP can precede symptoms of SS, and (iii) treatment decision for asymptomatic patients with abnormal imaging or patients with mild severity should be weighed between the risk of immunosuppression and risk of active disease.